African university students, the five factor model, and parental bonding : prediction of alcohol use - Mhlongo, Mpumelelo Marcel (My University, 2008)
There is a considerable literature linking aspects of personality, parenting, and risk behaviors such as alcohol abuse. Three hundred African university students participated in a study of the relationship between personality, assessed with the NEO PI-R (Costa & McCrae, 1992), and alcohol use. Personality traits did not predict alcohol use among the students. It was also predicted that the Parental Bonding Instrument (PBI; Parker, Tupling, & Brown, 1979) would mediate the relationship between personality and alcohol use. Results of the current study revealed no significant relationship between parenting and alcohol use. The results are discussed with regards the use of the NEO PI-R’s validity in the population used. Keyword: Five Factor Model; Parental bonding; Abstainers; Moderate drinkers; Heavy drinkers.
Thesis (M.Ed.) (Clinical Psychology) --University of Limpopo, 2008.
Keywords: Substance abuse.; Five Factor Model; Parental bonding; Abstainers; Moderate drinkers; Heavy drinkers; 616.8619096; Alcohol beverages - South Africa.; Substance abuse.